The Impact of ESG Scores on Financial Performance and Risk: Insights from the Finnish Market (2010– 2022) - Laaksonen, Elias (My University, 2024)
Sustainable investing has gained significant popularity in recent decades, leading companies and investors to consider its impact on the financial markets. This study aims to investigate the relationship between ESG (Environmental, Social, Governance) scores and both equity returns and risk. The ESG score is a measurement to assess a company's sustainability in three areas: environment, social responsibility, and governance. Previous studies have shown conflicting results on the relationship between sustainability and equity returns and risk. Some studies indicate that sustainable companies perform better and are less risky, whereas other studies suggest the contrary. The prior study results may vary depending on the geographical area, the period considered, and the methods used. This study focuses on Finnish listed companies in 2010–2022, analysing 581 observations with available ESG scores and annual return data. Finnish companies are known as pioneers in ESG practices and ESG reporting, making the Finnish stock market an ideal case study. The study uses quantitative methods to investigate the links between ESG factors, equity re-turns and risk. Both single-variate and multivariate regression models are utilised to analyse the data. The relationship between ESG factors and equity returns is examined at both the portfolio and company levels. At the portfolio level, companies are divided into portfolios with a top 25% ESG score and a bottom 25% ESG score to assess the relevance of ESG scores to performance metrics. The results show that at the portfolio level, a portfolio with a lower ESG score has outperformed on average across all performance indicators, including annual return, Sharpe ratio, and Jensen's Alpha. However, portfolio-level results did not prove to be statistically significant. Similarly, no statistically significant link was found at the company level between sustainability and performance indicators. However, using a simple regression mod-el, statistically significant associations were found between ESG scores and stock risk. The ESG combined score, as well as the E and S pillar scores, were statistically significantly negatively correlated with risk, indicating that sustainable companies tend to experience lower risk. When the company's market capitalisation, debt % and beta values were included as control variables, the statistical significance of ESG and the E and S pillars was no longer observed. Instead, G-pillar scores became statistically significant and positively correlated with risk, indi-cating that companies with higher G-pillar scores might experience higher stock risk. These findings suggest that the statistical significance of ESG scores and their correlation with risk is context-dependent and influenced by control variables.

Vastuullisesta sijoittamisesta on tullut entistä suositumpaa viimeisten vuosikymmenten aikana, minkä vuoksi sekä yrityksissä että sijoittajien keskuudessa on alettu kiinnittää huomiota vastuullisuuden vaikutuksiin osakemarkkinoilla. Tässä tutkimuksessa pyritään selvittämään ESG-pisteiden (Environmental, Social, Governance) sekä osakkeiden tuoton ja riskin välistä yhteyttä. ESG-pisteytyksellä arvioidaan yrityksen vastuullisuutta kolmella eri osa-alueella: ympäristö, yhteiskuntavastuu ja hyvä hallintotapa. Aiemmat tutkimukset ovat osoittaneet ristiriitaisia tuloksia vastuullisuuden suhteesta osakkeiden tuottoihin ja riskiin. Osa tutkimuksista on havainnut, että vastuulliset osakkeet suoriutuvat paremmin ja ovat vähemmän riskisiä, kun taas osa tutkimuksista on saanut päinvastaisia tuloksia. Aiemmat tutkimustulokset voivat vaihdella maantieteellisen alueen, tarkastelujakson sekä käytettyjen menetelmien vuoksi. Tässä tutkimuksessa keskitytään suomalaisiin pörssiyrityksiin vuosina 2010–2022, joille on saatavilla ESG pisteytys ja vuosittainen tuottoindeksi. Kokonaisuudessaan tutkimuksessa on hyödynnetty 581 havaintoa. Suomalaiset yhtiöt tunnetaan edelläkävijöinä ESG-käytännöissä ja niiden raportoinnissa, mikä tekee Suomen osakemarkkinoista hyvän tapaustutkimuksen. Tutkimuksessa käytetään kvantitatiivisia menetelmiä ESG-faktoreiden, osaketuottojen ja riskin välisten yhteyksien selvittämiseksi. Käytössä ovat sekä yksimuuttuja- että monimuuttujaregressiomallit. ESG faktorien ja osaketuottojen välistä yhteyttä tarkastellaan sekä portfolio- että yritystasolla. Portfoliotasolla yritykset on jaettu ylimmän 25 % ESG-pisteytyksen ja alimman 25 % ESG-pisteytyksen portfolioihin, jotta voidaan arvioida ESG-pisteiden merkitystä tuottomittareihin. Tulokset osoittavat, että portfoliotasolla matalamman ESG-pisteytyksen portfolio on tuottanut keskimääräisesti paremmin kaikilla tuottomittareilla, eli vuosituotolla, Sharpe-luvulla ja Jensenin Alphalla. Portfoliotason tulokset eivät kuitenkaan osoittautuneet tilastollisesti merkittäviksi. Myöskään yritystasolla tarkasteltuna, ei havaittu tilastollisesti merkittävää yhteyttä vastuullisuudella ja tuottomittareilla. Yksinkertaisella regressiomallilla tarkasteltuna ESG-pisteiden ja osakkeen riskin välillä havaittiin tilastollisesti merkittäviä yhteyksiä. ESG, sekä E ja S pilareiden pisteet negatiivisesti korreloivat riskin kanssa, mikä tar-koittaa, että vastuullisemmat yritykset kokevat pienempää riskiä. Kun malliin lisättiin kontrollimuuttujina yrityksen markkina-arvo, velkaantuneisuusaste sekä beta-arvot, ESG:n sekä E- ja S-pilarien tilastollinen merkittävyys hävisi. Sen sijaan G-pilarin pisteet muuttuivat tilastollisesti merkittäviksi korreloiden positiivisesti riskin kanssa. Tulokset osoittavat, että ESG-pisteiden tilastollinen merkityksellisyys ja riskin kanssa havaittu korrelaatio ovat riippuvaisia kontekstista ja kontrollimuuttujista.
Keywords: riskienhallinta; vastuullisuus; vastuullinen sijoittaminen; sijoitustoiminta; yritysvastuu; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance